Sinonasal neoplasms in 49 dogs: clinical, macroscopic, and histopathological aspects - Ricaldi,Giulia F.S. (2020)
ABSTRACT: This study aimed to quantify nasosinusal neoplasms diagnosed in dogs in 20 years (2000-2019) and characterize the main clinical, macroscopic, and histological aspects of these neoplasms. The sex, breed, age, skull conformation, the main clinical signs, and the anatomopathological characteristics (distribution, macroscopy, and histology) were computed. During this period, 49 dogs were affected by neoplasms in these regions, totaling 50 neoplasms (one dog had two neoplasms of different locations and histogenetic origins). Similar amounts of mixed-breed dogs (25/49) and purebred dogs (24/49) were affected, these distributed in 16 breeds. Among purebreds, it was noted that dogs with mesocephalic cranial conformation (12/24) were the most affected, followed by dolichocephalic (10/24) and brachycephalic (2/24). There were 22 cases in males and 27 in females, making a proportion of 1:1.23. There was an age variation from 11 months to 16 years old. The epithelial neoplasms have occurred in older dogs compared to those of other histogenic origins (mesenchymal and other origins/round cells). The main clinical signs were similar between the histogenetic categories, related to the involvement of the upper respiratory tract, sometimes accompanied by nervous signs (when there was brain invasion of nasal neoplasms or vice versa). The possible origin site was mostly in the nasal cavity concerning the paranasal sinuses (and other locations). Invasions occurred in different tissues adjacent to the nasal cavity and paranasal sinuses, resulting in cranial and facial deformities (21/49). The frequency was 48% of epithelial neoplasms, 32% of mesenchymal neoplasms, and 10% of neoplasms with other origins and round cells. The neoplasms most frequently observed, in decreasing order of frequency, were: adenocarcinoma (9/50), squamous cell carcinoma (9/50), transmissible venereal tumor (5/50), osteosarcoma (5/50), chondrosarcoma (4/50), and undifferentiated sarcoma (4/50). Through this study, it was possible to establish the frequency of these neoplasms in 20 years and their clinical, macroscopic, and histological characteristics.